ON THE ISSUE OF LEGAL SYSTEM’S DIGITAL TRANSFORMATION: HUMAN RESOURCES’ UPGRADING - Andreyanova, Inna; Rozhkova, Anna (Administrative and Criminal Justice, 2019)
In the information and digital environment, the transformation of the legal system is becoming topical and is being updated, including state authorities of all levels as well as the regulatory legal system, regulation-making, law enforcement and judicial practice, the powers of officials and subjects of legal relations in order to comply with such principles as openness, accessibility, legality, public control. In this regard, the transformation will first of all affect the specialists in the field of jurisprudence, whose competencies are being formatted at the intersection of information, digital and legal areas in the creation process of the updated legal system base. In this context, scientific and educational institutions of the highest level are assigned to implement a strategic task to update the new professions in the field of law at institutional level. The aim of the research work is to identify some relevance aspects of law education transformation. The problem of research work is linked with contradictions at the job market due to the low demand for former professions as well as the depreciation of the educational system because of the lack of technology in the development of educational and other alternative forms of education on platforms and profile platforms. The novelty of the research work is expressed by the practical application of the institutional approach to the implementation of professional standards in qualifications’ updating through network collaborative educational and project programmes. The conclusions of the research work are expressed in the concept of professional standards’ implementation; development of network collaborative educational programmes; module and project training as the main tools for legal professions’ modification.